Assessment of Residents Level of Knowledge in Pharmacovigilance - OUNI, Bouraoui; MANSOUR, Khadija; HARRATH, Fatma; SLIM, Raoudha; AKKARI, Imen; FATHALLAH, Neila; BENSAYED, Nesrine (Archives of Clinical and Medical Case Reports, 2024)
Introduction: Pharmacovigilance is a discipline aimed at monitoring, evaluating, managing, and pre-venting the adverse effects resulting from the use of medications. It is crucial in everyday medical practice and contributes to ensuring patient safety by identifying and managing the risks associated with drugs. Objective: To assess the level of knowledge among residents in Tunisia regarding pharmacovigilance, with the aim of proposing a strategy to raise awareness in this field. Materials and Methods: A cross-sectional observational study was conducted to evaluate the knowledge of residents (across all specialties) in pharmacovigilance. Data were collected using an anonymous questionnaire that included personal and professional information, knowledge about pharmacovigilance, reasons for underreporting adverse effects, and suggested corrective actions. The variables studied encompassed personal and professional factors, pharmacovigilance training, information sources, knowledge, and attitudes towards the reporting system. Statistical analysis was performed using the SPSS software, and a literature search was conducted to support the study. Results: The survey conducted among 511 residents revealed that 65% were females and 35% were males. The most common medical specialty was general medicine with 36.6% of participants, followed by family medicine (34.6%) and surgical specialties (28.8%). The majority of residents were in their first year (35%), followed by second year (24.9%) and third year (23.7%). Regarding the residents’ knowledge of pharmacovigilance, 87.1% had heard about it during their medical studies. The majority (83%) accurately defined pharmacovigilance as the detection, evaluation, understanding, and prevention of adverse effects. However, almost all residents were not aware of the Tunisian pharmacovigilance system (53.2%) or the Sousse Regional Pharmacovigilance Center (30.1%). Regarding the residents’ knowledge of pharmacovigilance, 61.4% knew that reporting adverse effects was mandatory, but only 29.2% were aware of the healthcare professionals involved in this reporting. The majority of residents were unfamiliar with causality assessment methods in pharmacovigilance (97.3%) and the timeframe for reporting a serious adverse effect (96.5%). Concerning the reporting of adverse effects, most residents knew they should report all types of adverse effects but believed they didn’t report enough (83.6%). The majority of residents reported adverse effects to the national/regional pharmacovigilance center (91.2%).